Alternative and augmentative communication in the speech and communication development process of children with autism spectrum disorder - Giziewska, Marta (Logopedia Silesiana, 2020)
The article presents issues related to speech and the more widely understood process of communication of children with the autism spectrum disorder. The determinants of speech development and communication of children with ASD were characterized. Efforts were also made to show the consequences of disturbed speech development translating into psychosocial functioning. The paper explains the notions of the alternative and augmentative communication and describes the most frequently used methods in the treatment of children with the autism spectrum disorder.